2015
DOI: 10.1007/s12013-015-0643-3
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin-Induced Apoptosis is Associated with Inhibition of Sarco/Endoplasmic Reticulum Calcium ATPase Activity in Colorectal Cancer

Abstract: Dihydroartemisinin (DHA) is a promising anti-cancer compound capable of inhibiting proliferation and inducing apoptosis of various cancer cells, including colorectal cancer. However, the molecular mechanisms have not been well understood. This study aimed to explore the underlying mechanism of DHA-induced apoptosis in HCT-116 cells. Cell counting kit-8 assay and flow cytometry analysis confirmed that DHA inhibited proliferation, arrested cell cycle at G0/G1 phase, and enhanced apoptosis in HCT-116 cells. Fluo-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…Our results showed that Z-VAD or 3-MA partly blocked the inhibitory effect of DHA on the cell viability, and Z-VAD combined with 3-MA completely rescued this effect, suggesting that the cytotoxic effects of DHA on human GBM cells was associated with cell apoptosis and autophagy. Consistent with our results, recent studies found that DHA induced apoptosis in human gastric cancer and colorectal cancer cells (Lu et al, 2015 ; Zhang et al, 2017 ), and effectively inhibited cell growth and induced apoptosis in human BT325 glioma cells and rat C6 glioma cells (Du et al, 2015 ). Furthermore, DHA possessed cytotoxic effects by inducing autophagy in human leukemia K562 cells and pancreatic cancer cells (Wang et al, 2012 ; Jia et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that Z-VAD or 3-MA partly blocked the inhibitory effect of DHA on the cell viability, and Z-VAD combined with 3-MA completely rescued this effect, suggesting that the cytotoxic effects of DHA on human GBM cells was associated with cell apoptosis and autophagy. Consistent with our results, recent studies found that DHA induced apoptosis in human gastric cancer and colorectal cancer cells (Lu et al, 2015 ; Zhang et al, 2017 ), and effectively inhibited cell growth and induced apoptosis in human BT325 glioma cells and rat C6 glioma cells (Du et al, 2015 ). Furthermore, DHA possessed cytotoxic effects by inducing autophagy in human leukemia K562 cells and pancreatic cancer cells (Wang et al, 2012 ; Jia et al, 2014 ).…”
Section: Discussionsupporting
confidence: 92%
“…DHA up-regulated ROS to increase ferrous ion in cells, and contributed to the apoptosis of human lung carcinoma cells (Xu C. C. et al, 2016 ). DHA increasing ROS resulted in the accumulation of intracellular Ca 2+ , and promoted the mitochondria and ER stress pathway of apoptosis in human colorectal cancer cells (Lu et al, 2015 ). Furthermore, previous study found that DHA induced autophagy and inhibited the growth of iron-loaded human myeloid leukemia cells via ROS toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, dihydroartemisinin chemotherapy induces mitochondria-dependent apoptosis via ER stress pathways in CRC HCT116 cells 162 . The ERN1-XBP1 pathway is also important for promotion and progression of CRC 163 .…”
Section: General Aspects Of the Unfolded Protein Responsementioning
confidence: 99%
“…The cytotoxicity of artemisinin-type molecules has also been linked to the endoplasmic reticulum (ER) stress pathway (18)(19)(20)(21). ER stress occurs when the load of unfolded proteins exceeds the protein folding capacity of the cell (22).…”
Section: Introductionmentioning
confidence: 99%